Rethinking spatial planning - Alison Todes (Town and Regional Planning, 2008)
In South Africa, broad spatial frameworks have become a standard form of planning, but have been critiqued on various grounds. This paper focuses on three lines along which spatial planning may be reconsidered. First, it argues that it is important for planners to engage with the complexity of the socio-spatial dynamics of the city. Secondly, it suggests that planners need a deeper understanding of urban economic space and a more conscious consideration of the way in which planning relates to markets. Thirdly, spatial planning could be enhanced by a stronger link to infrastructure planning.